Industrial competitiveness of the auto parts industries in four large Asian countries : the role of government policy in a challenging international environment - Doner, Richard F. (World Bank Policy Research Working Paper, 2006)
Rationalization and stabilization following the Asian financial crisis of the late 1990s combined with the expansion and liberalization of regional and global trade to create significant parts industries in China, Indonesia, and the Republic of Korea. Conventional policies of stabilization and liberalization, however, cannot fully explain growth patterns. Japan and Korea grew into major players before liberalizing trade and investment, while even after extensive liberalization Indonesia has yet to move from extensive to intensive growth. These anomalies suggest that to explain success in the auto parts industry we need to move beyond liberalization to look at policies and institutions promoting economies of scale, skill formation, quality upgrading, supplier-linkage cooperation, and innovation. In Japan, the regional and global leader, innovative assemblers led industrial development and supported key suppliers, but the government also supported diffusion of quality control techniques and new technology to small and medium enterprises, and encouraged stable employment among core employees. Korea remains weaker on both small and medium enterprise and employment fronts, but government-encouraged consolidation around a small number of business groups, an extended period of protection, and support for export promotion led to economies of scale. Liberalization of foreign investment after the financial crisis helped ameliorate the excessive statism of earlier policies and strengthened the parts industry. In China, liberalization for WTO entry, rapid expansion in demand, and strong support by local governments encouraged a wave of foreign investment in both assembly and parts. In contrast, institutional weaknesses continue to constrain development opportunities in Indonesia